Effect of pycnocline thickness on internal solitary wave breaking over a slope. (15th June 2021) - Nakayama, Keisuke; Iwata, Ryo; Shintani, Tetsuya
Abstract: When an internal solitary wave (ISW) breaks over a sloping bottom in the ocean, turbulent mixing causes energy dissipation that is associated with the breaking type. In a two-layer fluid, when pycnocline thickness is negligible, the breaking can be categorized into one of four breaker types: surging, plunging, collapsing, and fission breakers. The latest classification into four breaker types is based on wave slope, bottom slope gradient and an internal Reynolds number. However, it was unknown if this classification can be applied to categorize the breaking of an ISW under thick pycnocline conditions. The present study uses two-dimensional numerical simulations to investigate energy dissipation due to an ISW breaking over a slope under changing pycnocline thickness. We found that the classification can categorize all breaker types even when pycnocline thickness varies. Also, the practical reflection coefficient, defined in this study, becomes smaller for collapsing and surging breakers with the increase in the pycnocline thickness due to an offshore shift in breaking points. In contrast, the practical reflection coefficient is found to be constant for plunging and fission breakers under changing pycnocline thickness. Highlights: All breaker types on a slope can be categorized when pycnocline thickness varies. Breaking point moves to offshore mainly under increasing pycnocline thickness. Energy dissipation does not change significantly under varying pycnocline thickness. Breaking point can be estimated by using a general breaking location.